The Rheological Properties and Structural Changes of Abalone Meat with Different Drying Methods. Issue 2 (7th February 2017) - Zhang, Zhaohui; Liu, Qian; Wang, Pei; Liu, Fan; Gao, Xin
ABSTRACT: Changes in tissue structure and rheological properties of abalone meat with cold air drying and natural drying were studied. Natural drying took 168 h, while cold air drying took 120 h, which was 71% of natural drying. Nutrition loss of cold air drying abalone meat was less than that of natural drying samples. Muscle fibers in heated samples reassembled, and voids in muscular tissue extended. With drying time increasing, muscle fibers in abalone meat shrank, and the size of aperture among myofibrils decreased. While drying finished, myofibrils in cold air drying abalone meat had a homogeneous network structure, which was fit for water restoration. Rheological properties (elasticity modulus E, viscosity modulus η, and rupture strength) in heated samples were smaller than those in raw samples, while the relaxation time τ was greater. During the drying process, E, η, and rupture strength tended to increase, and the relaxation time τ had no significant regularity changes. Compared with natural drying, the cold air drying had more advantages in actual production as the drying time was shorter, and the drying process and sanitary conditions were easy to control.